Climate Noise Influences Ice Sheet Mean State - Lu Niu; Gerrit Lohmann; Evan J. Gowan (Geophysical Research Letters)
Abstract Evidence from proxy records indicates that millennial‐scale abrupt climate shifts, called Dansgaard‐Oeschger events, happened during past glacial cycles. Various studies have been conducted to uncover the physical mechanism behind them, based on the assumption that climate mean state determines the variability. However, our study shows that the Dansgaard‐Oeschger events can regulate the mean state of the Northern Hemisphere ice sheets. Sensitivity experiments show that the simulated mean state is influenced by the amplitude of the climatic noise. The most likely cause of this phenomenon is the nonlinear response of the surface mass balance to temperature. It could also cause the retreat processes to be faster than the buildup processes within a glacial cycle. We propose that the climate variability hindered ice sheet development and prevented the Earth system from entering a full glacial state from Marine Isotope Stage 4 to Marine Isotope Stage 3 about 60,000 years ago.